RETRACTED ARTICLE: Dietary polyphenols and the risk of metabolic syndrome: a systematic review and meta-analysis - Pushpamala Ramaiah; Kamilya Jamel Baljon; Ahmed Hjazi; Maytham T. Qasim; Omar Abdulwahid Salih Al-ani; Shad Imad; Beneen M. Hussien; Ali Alsalamy; Nazila Garousi (BMC Endocrine Disorders)
Abstract Background Accumulating evidence has suggested that dietary polyphenols may be protective against metabolic syndrome (MetS); however, the available evidence is contradictory. The aim of this meta-analysis was to assess the association between dietary intake of polyphenols and the odds of MetS. Methods The PubMed and Scopus databases were systematically searched to obtain eligible studies. The risk of MetS for the highest versus the lowest intakes of total, subclasses and individual polyphenols were examined by pooling odds ratios (OR) and 95% confidence intervals (95%CI) using the random effects model. Results A total of 14 studies (6 cohort and 8 cross-sectional studies) involving a total of 50,366 participants with 10,879 cases of MetS were included. When various polyphenol compounds were pooled, they were significantly related to a 22% decreased odds of MetS (([5 studies]; OR: 0.78; 95%CI: 0.72–0.85). Higher intakes of total flavonoids (([9 studies]; OR: 0.78; 95%CI: 0.72–0.85), flavan-3-ols (([2 studies]; OR: 0.64; 95%CI: 0.43–0.94), isoflavones (([3 studies]; OR: 0.84; 95%CI: 0.75–0.93), stilbenes (([4 studies]; OR: 0.86; 95%CI: 0.76–0.97), flavones (([2 studies]; OR: 0.79; 95%CI: 0.71–0.89), and quercetin (([2 studies]; OR: 0.63; 95%CI: 0.43–0.93) were also significantly associated with a decreased risk of MetS. The associations were not modified by the age of the participants. No association was found for total polyphenols, phenolic acids, lignans, anthocyanins, and flavonols. Conclusion The results of this meta-analysis supported that higher polyphenol intake can lower the risk of MetS.